Expression Profile of Wnt/β-Catenin Signalling Molecules and the Wnt Antagonist Secreted Frizzled-Related Protein 4 in Apoptosis in Breast Cancer Tissue Micro-Arrays - Berry, A.; Charles, A.; Zeps, N.; Cregan, D.; Arfuso, Frank; Dharmarajan, Arunasalam (Lifescience Global, 2014)
Wnt proteins are often up-regulated in cancer. The secreted frizzled-related proteins (sFRPs) can abrogate Wnt signalling and are involved in apoptosis. We investigated the expression of Wnt1, β-Catenin, and an antagonist, sFRP4, as well as apoptosis in breast cancer using tissue micro-arrays (TMAs) comprising 191 tissue cores. Results demonstrated stronger staining intensity for Wnt1 in tumour versus non-tumour samples (p<0.05). Epithelial sFRP4 did not differ between invasive and non-invasive tissue; however, there was increased sFRP4 expression in the blood vessels and lymphocyte cells of tumour compared to non-tumour tissue. These data suggest Wnt involvement in determining the breast cancer phenotype and highlight a potential new role for sFRP4 as a diagnostic/prognostic marker.